2018
DOI: 10.1097/scs.0000000000004346
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopically Assisted Modified Caldwell-Luc Approach to Enucleation of Dentigerous Cyst With Ectopic Tooth From the Maxillary Sinus

Abstract: Dentigerous cysts in the craniomaxillofacial complex are a benign pathology commonly associated with ectopically placed teeth. Owing to slow and asymptomatic growth, they often attain considerable size before diagnosis that may compromise adjacent anatomical structures. Various techniques for removal of dentigerous cysts from the maxillary sinus have been described. This case report demonstrates a hybrid endoscopically assisted modification of the Caldwell-Luc approach to provide the technical advantages of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…9 Unfortunately, all previous studies in the literature are cross-sectional observations or case reports, and no studies have focused on the process of ectopic tooth formation. [2][3][4][5]9,10,16 Fortunately, in the present study, the dynamic process of the formation of an ETm in a young person was observed for the first time through follow-up examinations (Figure 2). An obvious ectopic tooth appeared at the age of 19 years in the posterior wall of the maxillary sinus; this tooth had been observed as only an area of soft tissue density and a small bone wall defect at the age of 16 years.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…9 Unfortunately, all previous studies in the literature are cross-sectional observations or case reports, and no studies have focused on the process of ectopic tooth formation. [2][3][4][5]9,10,16 Fortunately, in the present study, the dynamic process of the formation of an ETm in a young person was observed for the first time through follow-up examinations (Figure 2). An obvious ectopic tooth appeared at the age of 19 years in the posterior wall of the maxillary sinus; this tooth had been observed as only an area of soft tissue density and a small bone wall defect at the age of 16 years.…”
Section: Discussionmentioning
confidence: 64%
“…The literature indicates that ectopic teeth are found mostly in adults. 9,10,16 However, ectopic teeth might also form after permanent teeth have developed. 9 Unfortunately, all previous studies in the literature are cross-sectional observations or case reports, and no studies have focused on the process of ectopic tooth formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of ectopic teeth usually comprises removal of the previous, taking into account its location and possible risks [ 4 ]. The traditional surgical approaches to maxillary sinus pathology are transoral Caldwell-Luc approaches or transnasal endoscopic surgery [ 5 , 12 ]. In recent literature, there is shift towards transnasal, endoscopic management of this pathology through a middle meatal antrostomy.…”
Section: Discussionmentioning
confidence: 99%